To divide fractions, you multiply the first fraction by the reciprocal of the second fraction.
The reciprocal of 4/5 is 5/4.
So, (-2/3/5) รท (4/5) is equal to (-2/3/5) x (5/4).
Multiplying the numerators and denominators, we get (-2/3/5) x (5/4) = (-2/1) x (1/1) = -2/1 = -2.
Therefore, the quotient when you divide -2/3/5 by 4/5 is -2.
What is the quotient when you divide -2/3/5 by 4/5
15 answers
solve for x please 3x + 2 = x + 8
To solve for x in the equation 3x + 2 = x + 8, we can start by isolating the variable term on one side of the equation.
First, we subtract x from both sides:
3x + 2 - x = x + 8 - x
2x + 2 = 8
Next, we subtract 2 from both sides:
2x + 2 - 2 = 8 - 2
2x = 6
To isolate x, we divide both sides of the equation by 2:
2x/2 = 6/2
x = 3
Therefore, x = 3 is the solution to the equation 3x + 2 = x + 8.
First, we subtract x from both sides:
3x + 2 - x = x + 8 - x
2x + 2 = 8
Next, we subtract 2 from both sides:
2x + 2 - 2 = 8 - 2
2x = 6
To isolate x, we divide both sides of the equation by 2:
2x/2 = 6/2
x = 3
Therefore, x = 3 is the solution to the equation 3x + 2 = x + 8.
Manipulate the equation y=5x-11 so that it is written in terms of x. Which equation is equivalent to y=5x-11?
To write the equation y = 5x - 11 in terms of x, we can manipulate it to isolate x on one side of the equation.
We start by adding 11 to both sides of the equation:
y + 11 = 5x - 11 + 11
Simplifying, we have:
y + 11 = 5x
Next, we can divide both sides of the equation by 5:
(y + 11) / 5 = 5x / 5
Simplifying further:
(y + 11) / 5 = x
Therefore, the equation equivalent to y = 5x - 11 in terms of x is x = (y + 11) / 5.
We start by adding 11 to both sides of the equation:
y + 11 = 5x - 11 + 11
Simplifying, we have:
y + 11 = 5x
Next, we can divide both sides of the equation by 5:
(y + 11) / 5 = 5x / 5
Simplifying further:
(y + 11) / 5 = x
Therefore, the equation equivalent to y = 5x - 11 in terms of x is x = (y + 11) / 5.
Charity is buying peaches at the store. The cost of the peaches are $1.30 per pound. If she has $6.50 to spend on peaches, how many pounds (x) can she buy?
Set up an equation to solve the problem.
Set up an equation to solve the problem.
To set up an equation to solve the problem, we can use the following information:
The cost of the peaches per pound is $1.30.
Charity has $6.50 to spend on peaches.
Let x be the number of pounds of peaches she can buy.
Since the cost of the peaches per pound is $1.30, the equation can be set up as:
1.30x = 6.50
This equation represents the total cost (1.30x) should be equal to the amount of money Charity has ($6.50).
Now, you can solve for x by dividing both sides of the equation by 1.30:
x = 6.50 / 1.30
Simplifying the division, we get:
x = 5
Therefore, Charity can buy 5 pounds of peaches with $6.50.
The cost of the peaches per pound is $1.30.
Charity has $6.50 to spend on peaches.
Let x be the number of pounds of peaches she can buy.
Since the cost of the peaches per pound is $1.30, the equation can be set up as:
1.30x = 6.50
This equation represents the total cost (1.30x) should be equal to the amount of money Charity has ($6.50).
Now, you can solve for x by dividing both sides of the equation by 1.30:
x = 6.50 / 1.30
Simplifying the division, we get:
x = 5
Therefore, Charity can buy 5 pounds of peaches with $6.50.
set up an equation to solve that problem pls
Apologies for the confusion. To set up the equation, let's use the following information:
The cost of the peaches per pound is $1.30.
Charity has $6.50 to spend on peaches.
Let x be the number of pounds of peaches she can buy.
Since the cost of the peaches per pound is $1.30, the equation can be set up as:
1.30x = 6.50
This equation represents that the total cost (1.30x) should be equal to the amount of money Charity has ($6.50).
Therefore, the equation to solve the problem is 1.30x = 6.50.
The cost of the peaches per pound is $1.30.
Charity has $6.50 to spend on peaches.
Let x be the number of pounds of peaches she can buy.
Since the cost of the peaches per pound is $1.30, the equation can be set up as:
1.30x = 6.50
This equation represents that the total cost (1.30x) should be equal to the amount of money Charity has ($6.50).
Therefore, the equation to solve the problem is 1.30x = 6.50.
Jackson solved the problem 3x-8=2(2x-7) using the following steps:
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step
The last step is to solve for x by using the Multiplication Property of Equality:
Multiplying both sides of the equation (-x) = -6 by -1, we get:
x = 6
Therefore, the last step is to determine that x is equal to 6.
Multiplying both sides of the equation (-x) = -6 by -1, we get:
x = 6
Therefore, the last step is to determine that x is equal to 6.
A computer technician charges a fixed amount for a repair, plus an additional amount per hour. The equation, y=45x+75, describes y, the total amount the technician charges, in dollars, based on x hours for the repair.
What is the meaning of the initial amount for the equation?
What is the meaning of the initial amount for the equation?
In the equation y = 45x + 75, the initial amount of $75 represents the fixed amount that the computer technician charges for a repair.
Even if the repair takes no time (x = 0), the initial fixed amount of $75 will still be charged. This initial amount covers the technician's baseline cost, such as overhead expenses, equipment usage, or the basic cost of examining and diagnosing the issue.
So, regardless of the number of hours worked, the computer technician will charge a minimum of $75 for their services.
Even if the repair takes no time (x = 0), the initial fixed amount of $75 will still be charged. This initial amount covers the technician's baseline cost, such as overhead expenses, equipment usage, or the basic cost of examining and diagnosing the issue.
So, regardless of the number of hours worked, the computer technician will charge a minimum of $75 for their services.
What is the first step to solve the inequality x-5<x/6
To solve the inequality x - 5 < x/6, the first step is to eliminate the fraction by multiplying both sides of the inequality by 6.
By doing this, we can eliminate the fraction on the right side of the inequality to have only whole numbers.
The inequality becomes:
6(x - 5) < x/6 * 6
Simplifying:
6x - 30 < x
Now we can continue simplifying and solving the inequality.
By doing this, we can eliminate the fraction on the right side of the inequality to have only whole numbers.
The inequality becomes:
6(x - 5) < x/6 * 6
Simplifying:
6x - 30 < x
Now we can continue simplifying and solving the inequality.